L'importance des cereales non traditionnelles dans la consommation des riches et des pauvres à Ouagadougou - Reardon, Thomas; Thiombiano, Taladidia; Delgado, Christopher L. (PERSEE Program, 1989)
Using a representative sample of the various types of households in the city of Ouagadougou, the authors analyzed the potential effects of a price rise for imported rice on food consumption. The inquiry contradicted their initial hypotheses which deemed that such a rise would boost the consumption of traditional cereals (millet and sorghum). This result is due to the low price elasticity of the demand for rice by the poorest households, which are compelled by their usual jobs to buy, for lunch, prepared rice from street vendors. Consequently the substitution is likely to be oriented to imported wheat rather than to the long to prepare traditional cereals which require considerable preparation time. However, a development can be foreseen for a consumption of corn, which can be cultivated in Burkina Faso.